Hormetic-Like Effects of L-Homocysteine on Synaptic Structure, Function, and Aβ Aggregation - Carla Montecinos-Oliva; Macarena S. Arrázola; Claudia Jara; Cheril Tapia-Rojas; Nibaldo C. Inestrosa (Pharmaceuticals, 2020)
Alzheimer’s Disease (AD) is the primary cause of dementia among the elderly population. Elevated plasma levels of homocysteine (HCy), an amino acid derived from methionine metabolism, are considered a risk factor and biomarker of AD and other types of dementia. An increase in HCy is mostly a consequence of high methionine and/or low vitamin B intake in the diet. Here, we studied the effects of physiological and pathophysiological HCy concentrations on oxidative stress, synaptic protein levels, and synaptic activity in mice hippocampal slices. We also studied the in vitro effects of HCy on the aggregation kinetics of Aβ40. We found that physiological cerebrospinal concentrations of HCy (0.5 µM) induce an increase in synaptic proteins, whereas higher doses of HCy (30−100 µM) decrease their levels, thereby increasing oxidative stress and causing excitatory transmission hyperactivity, which are all considered to be neurotoxic effects. We also observed that normal cerebrospinal concentrations of HCy slow the aggregation kinetic of Aβ40, whereas high concentrations accelerate its aggregation. Finally, we studied the effects of HCy and HCy + Aβ42 over long-term potentiation. Altogether, by studying an ample range of effects under different HCy concentrations, we report, for the first time, that HCy can exert beneficial or toxic effects over neurons, evidencing a hormetic-like effect. Therefore, we further encourage the use of HCy as a biomarker and modifiable risk factor with therapeutic use against AD and other types of dementia.